PANORAMIC VIEW OF CHALLENGES AND OPPORTUNITIES FOR PRIMARY HEALTHCARE SYSTEMS IN PAKISTAN - Sharif, Hina; Sughra, Ume; Butt, Zahid (Journal of Ayub Medical College Abbottabad, 2016)
Background: Pakistan has a broad system of primary health care facilities to achieve mission of Health for all. Over the last seven years health expenditure by government of Pakistan has been increased to attain this goal. This study was conducted with the aim to assess all blocks of service readiness (basic equipment, basic amenities, laboratory capacity, standard precautions and essential medicines) in public-primary health care facilities of tehsil Rawalpindi, Pakistan. Methods: A cross-sectional survey was carried out utilizing two separate structured questionnaires for basic health units and rural health centres. Information was collected from administrative heads along with other staff where required, of all public-primary health care facilities of Tehsil Rawalpindi. Data were analysed by using SPSS version.17. Results: A total of 26 health facilities were assessed; only 56% BHUs had a sign board that was available in readable form. BHUs with women medical officer as administrative head constituted 52%. Backup for electricity and toilet were the most neglected areas. Basic amenities, standard precautions and laboratory capacity of Basic Health Units (BHUs) showed a clear deviation from standards and is thus a challenge for Pakistan's Primary Health care (PHC). On the other hand for Rural Health Centres (RHCs), most were on the way to meet expectations. Conclusion: Pakistan's government is undoubtedly putting efforts in order to achieve targets of primary healthcare but it needs better mainstreaming of political, institutional and social commitments with modified standards for PHC. Keywords: Health systems; Primary healthcare; Service readiness; Healthcare facilities